Mixtures of per- and polyfluoroalkyl substances (PFAS) alter sperm methylation and long-term reprogramming of offspring liver and fat transcriptome - DruAnne L. Maxwell; Oladele A Oluwayiose; Emily Houle; Katherine Roth; Karolina Nowak; Savni Sawant; Amanda L. Paskavitz; Wanqing Liu; Katherine Gurdziel; Michael C. Petriello; J. Richard Pilsner (Environment International, 2024)
Male fertility has been declining worldwide especially in countries with high levels of endocrine disrupting chemicals (EDCs). Per- and polyfluorinated alkyl Substances (PFAS) have been classified as EDCs and have been linked to adverse male reproductive health. The mechanisms of these associations and their implications on offspring health remain unknown. The aims of the current study were to assess the effect of PFAS mixtures on the sperm methylome and transcriptional changes in offspring metabolic tissues (i.e., liver and fat). C57BL/6 male mice were exposed to a mixture of PFAS (PFOS, PFOA, PFNA, PFHxS, Genx; 20 µg/L each) for 18-weeks or water as a control. Genome-wide methylation was assessed on F0 epidydimal sperm using reduced representation bisulfite sequencing (RRBS) and Illumina mouse methylation array, while gene expression was assessed by bulk RNA sequencing in 8-week-old offspring derived from unexposed females. PFAS mixtures resulted in 2,861 (RRBS) and 83 (Illumina) sperm DMRs (q < 0.05). Functional enrichment revealed that PFAS-induced sperm DMRs were associated with behavior and developmental pathways in RRBS, while Illumina DMRs were related to lipid metabolism and cell signaling. Additionally, PFAS mixtures resulted in 40 and 53 differentially expressed genes (DEGs) in the liver and fat of males, and 9 and 31 DEGs in females, respectively. Functional enrichment of DEGs revealed alterations in cholesterol metabolism and mitotic cell cycle regulation in the liver and myeloid leukocyte migration in fat of male offspring, while in female offspring, erythrocyte development and carbohydrate catabolism were affected in fat. Our results demonstrate that exposure to a mixture of legacy and newly emerging PFAS chemicals in adult male mice result in aberrant sperm methylation and altered gene expression of offspring liver and fat in a sex-specific manner. These data indicate that preconception PFAS exposure in males can be transmitted to affect phenotype in the next generation.